HBR's 10 must reads on strategy (Boston, Mass., 2011)
This book introduce distinguish your company from rivals. Clarify what your company will and won't do. Craft a vision for an uncertain future. Create blue oceans of uncontested market space. Use the Balanced Scorecard to measure your strategy. Capture your strategy in a memorable phrase. Clarify decision rights for faster decision making.
Keywords: Kế hoạch chiến lược,Strategic planning